Positive effects of durian fruit at different stages of ripening on the hearts and livers of rats fed diets high in cholesterol - Leontowicz H. (2017)
Aim of the study: Diets containing high cholesterol levels led to atherosclerosis damage in the livers and hearts of rats. The aim of this study was to investigate the possible positive effects of durian fruit against high-cholesterol diets. Materials and methods: Durians at various stages of ripening (young, mature, ripe and overripe) were chosen for in vitro and in vivo studies. In the in vivo study 36 male Wistar rats were divided into 6 groups and supplemented with cholesterol and durians. The bioactivity in vitro, plasma lipids, antioxidant activity, liver enzymes and histopathology of the aorta and liver were analyzed. Results: Polyphenols and flavonoids were significantly higher in the overripe durian, while quercetin, ascorbic acid and anthocyanins were more abundant in the ripe fruit and tannins - in mature samples (P < 0.05). The highest antioxidant potential was in overripe fruit and only the value of FRAP - in ripe durian samples (P < 0.05). The interaction between polyphenol extracts of ripe durian and BSA had a strong ability comparable to that of quercetin - to quench the intrinsic fluorescence of BSA by forming complexes. The main histopathological changes were detected in the liver and aorta of rats fed a high-cholesterol diet without fruit supplementation. These changes were minor in rats of Chol/DRipe (P < 0.05). Conclusion: Durian at different stages of ripening, especially ripe durian, constitute an excellent source of effective natural compounds with antioxidant and health-protective activity in general and liver and heart-protective effect in cholesterol fed rats in particular. © 2011 Elsevier GmbH.